EARLY STUDY OF AQUATIC BIODIVERSITY IN TEUPIN LAYEU IBOIH SABANG FOR MARINE ECOTOURISM - Dian Aswita; M Ali Sarong; Sugianto Sugianto (SCAD Independent, 2015)
Biodiversity is the diversity of organisms that indicate the overall variation of genes, species, and ecosystems in a region. This research aims to investigate the aquatic biodiversity in Teupin Layeu Iboih beach Sabang for resources marine ecotourism. The research was carried out from March to June 2014. A descriptive approach was applied to present the research findings to show biodiversity of the Teupin Layeu Iboih. The results of the research found 71 species of coral fish, 21 species of coral, and 15 species of aquatic invertebrates. Biodiversity were found in Teupin Layeu Iboih beach was varied and could be used for attraction in the development of marine ecotourism. Therefore, tourism activity that could be sustainable without being damaged by the nature.